Ethnobotanical Study on Tidung Tribe in Using Plants for Medicine, Spice, and Ceremony - Listiani Listiani; Fadhlan Muchlas Abrori (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2018)
Ethnobotany is a study that is related to plants and their use. This study is based on the reality that human kinds cannot be separated from their nature. Interestingly, different tribes has different ways in using natural resources. In in Indonesia, study ethnobotany has enriched the variety of ethnobiology study. This is because Indonesia has various tribes and each tribe has their own ways in interacting with their nature, including the way they use plants for daily life. One of tribes that has been studied is Tidung. Tidung is a tribe that inhabits the north area of Kalimantan, Indonesia. This tribe is using plants for medicine, spice, and ceremony. This study has been done by interviewing people who are Tidung tribe. The result shows that there are 20 medicinal plant species, 16 spice plant species, and eight ceremonial plant species. Mostly, the Tidung tribe use plants for medicine which means that this tribe highly depends on the nature of mainataining their health.